2021
DOI: 10.1021/acsomega.1c03150
|View full text |Cite
|
Sign up to set email alerts
|

Anionic-Surfactant-Stabilized Hydrophobic Ionic-Liquid-Based Bicontinuous Microemulsion as a Medium for Enzymatic Oxidative Polymerization of Aniline

Abstract: The hydrophobic ionic liquid [C8mim]­[PF6] (1-octyl-3-methylimidazolium hexafluorophosphate)-based bicontinuous microemulsion stabilized by the anionic surfactant [C4mim]­[AOT] (1-butyl-3-methylimidazolium bis­(2-ethylhexyl) sulfosuccinate) was first tried as a medium for horseradish peroxidase (HRP)-triggered oxidative polymerization of aniline. The effects of the mass ratio of [C8mim]­[PF6]-to-water (α), the mass fraction of [C4mim]­[AOT] in the total mixture (γ), and temperature (T) on the enzymatic polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
4
1
Order By: Relevance
“…It is shown that as γ increases both the peak position and the peak intensity have small changes, and the derived d values also vary slightly. These results are quite different from these derived in classical oil‐water BME due to the relatively poor surfactant efficiency in the HIL‐based BME against the classical oil‐water BME [11a,13,17] . The fact that the yield increases with increasing γ is probably due to the increased interfacial area and therefore the enhanced lipase activity.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…It is shown that as γ increases both the peak position and the peak intensity have small changes, and the derived d values also vary slightly. These results are quite different from these derived in classical oil‐water BME due to the relatively poor surfactant efficiency in the HIL‐based BME against the classical oil‐water BME [11a,13,17] . The fact that the yield increases with increasing γ is probably due to the increased interfacial area and therefore the enhanced lipase activity.…”
Section: Resultscontrasting
confidence: 60%
“…The smaller the microdomain size, the stronger the interfacial effect on lipase. As confirmed in Figure 5, the peak positions of the fluorescence spectra of lipase (caused by its endogenous fluorescent groups) in both BMEs are close to each other, but the fluorescence intensity in the mixed SB‐8/SB‐16 system is higher than in the single SB‐12 system, indicating stronger interaction between the interface and the solubilized lipase and therefore lower lipase activity [13,17] …”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…1). As monomers, either aniline, [1][2][3][4] the aniline dimer p-aminodiphenylamine (PADPA) 5 (Fig. 1), or mixtures of aniline and PADPA 6 were used.…”
Section: Introductionmentioning
confidence: 99%
“…SAILs have a distinctive solvation environment, and the Coulombic and ionic interactions, together with weak intermolecular interactions, result in hierarchical nanosegregated domains. The benefits of IL-based MEs and their potential for improved efficacy of conventional MEs in various applications have been studied as well. In recent past, extensive research on IL-based MEs has been documented, with an emphasis on their microstructure and physicochemical characteristics . The literature has reported instances of numerous conventional surfactants forming dry micelles in an IL medium .…”
Section: Introductionmentioning
confidence: 99%